Biomassa, crescimento e características funcionais de progênies de Parkia multijuga (Benth.) em plantação florestal - Rodrigues, Arrildo Filipe Silva (Ciências de Florestas Tropicais - CFT, 2024)
The establishment of commercial forests with native tree species is an important strategy for the recovery of deforested areas, as well as for the conservation of genetic heritage and income generation on rural properties in the Amazon. In commercial plantations for timber production, both the productivity and uniformity of trees are desirable traits. Such results can be obtained from the identification and selection of the best genotypes of a given commercial species. However, for native forest species in the Amazon, the genotypic selection stage has not been widely considered in the implementation of forest plantations. In addition to identifying the growth potential of trees, understanding the functional mechanisms associated with performance differences (e.g., growth and biomass accumulation) can be important for the selection of indicators for genetic improvement purposes. In the present study, the general objective was to evaluate the productivity of trees in a Parkia multijuga forest plantation, as well as the functional mechanisms that determine their intraspecific variation. The study was carried out from a progeny test experiment of the tree species P. multijuga, which was installed in July 2015 at the Experimental Farm of the Federal University of Amazonas (FAEXP-UFAM). The experimental design consisted of randomized blocks with 14 treatments (progenies) and 6 repetitions (blocs), for a total area of 0.3 hectares. The progenies were evaluated at seven years of age based on growth traits (diameter and height increment), biomass and volume accumulation, and leaf and crown traits. The P. multijuga progenies presented high survival values after seven years of planting. Most of the analyzed traits, such as crown area (6.27-15.88 m²), crown proportion (21.5-46.01%), biomass (1.4-6.0 t ha-1 year-1), and volume (0.87-2.1 m³ ha-1 year-1), exhibited strong intraspecific variation. Progeny 11 had the greatest increase in height, while progeny 6 had the greatest increase in collar diameter and volume and biomass. Physiological traits at the leaf level did not differ between progenies and had individually weak associations with growth variables. However, a multiple model combining physiological traits and canopy morphometry (photosynthesis (Pn), stomatal conductance (gs), crown area (ca), crown length (cl) and crown proportion (cp)) explained 73% of the intraspecific variation in tree biomass accumulation. The results suggest high variation in the field performance of P. multijuga progenies in forest plantations, which may be partly associated with differences in light interception capacity by the canopies and in carbon capture rates at the leaf level.
Keywords: Reflorestamento; Características foliares; Espécie arbórea nativa